Increasing the Quality of Garlic (Allium sativum L.) against the Provision of Foliar Fertilizer and Long Induction of SIPLO - Sugiarto Sugiarto; Rose Novita Sari Handoko (Indonesian Journal of Environment and Sustainable Development, 2020)
Garlic (Allium sativum L.) is one of the crops of economic importance that has increased considerably in recent years in Indonesia. Garlic roots have endophytic bacteria with the potential to promote plant growth, which is support in agriculture. Improving the quality and quantity of garlic can be done through the improvement of cultivation. Intensification of local potential systems techniques is a novel technology using electricity induction to improve physical chemical and biological properties in the soil. The electricity induction applied to the soil would increase ion and cation exchange in the ground. SIPLO is a new technology in agriculture and easy to improve for farmers. The result of combination foliar fertilizer and SIPLO were shown a good impact of the application to the production. Induction of SIPLO for 60 minutes and foliar fertilizer of 150 ml / l gave positive results for garlic production.